Peran strategis Ulama dalam Sosialisasi Bank Syariah - Sakinah Sakinah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
Clerics is a leader who has the charisma in the eyes of society. What is said, exemplified by clerics be an interesting thing for the community. He holds a very glorious and special viz as the inheritors of the Prophet. As the inheritors of the Prophet. As heir of the Prophet, Clerics have the roles, functions, and strategic position in delivering a moral message to the nation due to its position this glorious, people glorify and personifying them. All the words and actions of the clerics bocome a role model of its community. One of functions of the clergy is to preach (suggest to do good deeds / merits) and away from the prohibitions of Allah ((nahi-munkar) in the affairs of religious, social, political, cultural, and others. In the field of economics known as Muamalah Maliyah rarely this role functionalized and submitted to societies. Aspects of material / study propaganda theologian still struggling in the field of fiqh be only, not much touching economics. Therefore, Clerics are expected to maximize their role in the community with a way to invite people carry out economic activities in accordance with Islamic law through the dissemination of Syari’a Banking which is one of many Syari’a Transactions. This aspect has not been widely communicated to the public.